A study of defect in crystal structure by electrical resistivity - Nguyen, Van Hieu (Journal of Technical Education Science, 2011)
We measured the electrical resistivity in the temperature range from 2K to 300K to study some information of nano crystal structure for the rare earths. The electrical resistivity follows the Matthiessen’s rule with five contributions. The contribution of electron –electron scattering is dominant at low temperature for the strongly correlated electron system. Therefore, the residual resistivity ratio values, ratio of resitivity at room temperature and resitivity at absolute zero, are estimated to know some parameters to indicate the quality of samples. Most of RRhIn5 single crystal compounds show the low defect in crystal structure. The small values of RRR in RRhIn5 (R= Dy, Ho, Tb, Er) indicate that some remained indium metals presented inside of these compounds, which must be taken into account during the measuring process. The resistivity data is also in good agreement with our recent SEM and EDX results.